Investigating the relationship between knowledge management and information literacy with organizational entrepreneurship of students and teachers of Farhangian University of Mazandaran - Hadiyan, Seyedeh Zinat; Babai, Zahra; Ranjbar, Somaye; Talebi, Somaye (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2021)
Background and Aim: Knowledge management is a useful tool for organizations to develop their capital, encourage innovation and entrepreneurship, and maximize optimal performance. The aim of this study was to investigate the relationship between knowledge management and information literacy with organizational entrepreneurship. Method: This research is applied in terms of purpose; In terms of nature, descriptive and in terms of method, correlation and statistical population, included all student teachers of Farhangian University of Mazandaran province in the academic year 2021-2022 in the number of 3600 people. According to Krejcie and Morgan sampling table, 351 people were selected by stratified random sampling by gender (female: 129 and male: 222). The measurement tools were standard questionnaires of knowledge management of Patrick et al. (2009), information literacy of Siamak and Davarpanah (2009) andorganizational entrepreneurship of Hill (2003). Results: At the significance level of α = 0.05, the findings showed that there is a significant positive relationship between knowledge management and organizational entrepreneurship. There is also a significant positive relationship between information literacy and organizational entrepreneurship. Regression analysis showed that the contribution of knowledge management and information literacy variables in predicting organizational entrepreneurship is different. Thus, compared to knowledge management, information literacy has a higher share in predicting organizational entrepreneurship (P < α = 0.05). Conclusion: Therefore, paying attention to the growth and development of information literacy and knowledge management in students and teachers of Farhangian University can lead to an increase in their organizational entrepreneurship.